Peningkatan Hasil Belajar Siswa melalui Metode Discovery Learning di MA Nurul Huda: Sebuah Penelitian Tindakan Kelas - Wahyudi, Endri; Saputra, Hengki (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Improving the quality of learning in Islamic education, particularly in fiqh subjects, requires the application of appropriate learning models that actively engage students in the learning process. Objective: This study aimed to determine the extent to which the discovery learning model improves student learning outcomes at MA Nurul Huda Tegal. Method: The research employed the Classroom Action Research (CAR) method and was conducted at Madrasah Aliyah Nurul Huda in 2023. Data were collected through observation, interviews, and tests/evaluations. The analysis focused on students' learning mastery scores. The CAR was carried out in four stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. Result: The findings showed that the implementation of the discovery learning model led to an improvement in student learning outcomes in fiqh subjects. Students became more involved in the learning process and demonstrated better understanding and performance across the assessment stages. Conclusion: The discovery learning model is effective in enhancing students’ learning outcomes. It encourages active participation and fosters the ability to generate and realize creative ideas relevant to real-life contexts. Contribution: This study provides valuable insights for educators in Islamic schools, highlighting the potential of discovery learning to improve student engagement and achievement, especially in abstract and conceptual subjects like fiqh.